Defining the Ideal Breast Reconstruction Procedure After Mastectomy From the Patient Perspective: A Retrospective Analysis. (April 2022) - Petrou, Ilias G; Thomet, Céline; Jamei, Omid; Modarressi, Ali; Kalbermatten, Daniel F; Pittet-Cuénod, Brigitte
Background: An increasing number of breast cancer patients undergo immediate or secondary breast reconstruction, but the ideal method in terms of patient satisfaction remains ambiguous. We compared the 3 most common breast reconstruction techniques to determine patient satisfaction and objective outcomes. Methods: Retrospective study of 184 patients with breast cancer who underwent a reconstructive procedure between 1993 and 2011 at our institution. Procedures evaluated were implant-based reconstruction (IBR) alone, latissimus dorsi (LD) flap reconstruction with/without implant, and deep inferior epigastric perforator (DIEP) free flap reconstruction. A retrospective patient satisfaction questionnaire was sent to all women. Twenty patients from each subgroup were matched to conduct a standardized objective assessment of the sensitivity of their reconstructed breast. A blinded photographic evaluation was also performed by 3 independent observers to assess the esthetic aspect and symmetry. Results: DIEP obtained significantly higher average scores regarding the esthetic outcome, immediate reconstruction impact, and overall score in the questionnaire evaluation. The IBR had the best results in the somatosensory evaluation, with DIEP scoring better than LD. DIEP received higher scores on average than LD for the criteria of size and symmetry in the esthetic evaluation. No statistically significant differences were observed between IBR and DIEP. Conclusions: Good results were reported overall for all breast reconstruction procedures, with more reserved scores for LD. The DIEP reconstruction appeared to be the most satisfactory and best experienced reconstruction method for patients, despite the complexity of the intervention. Clinicians should be encouraged to consider DIEP as the principal choice for breast reconstruction.